Workshop on Principles of Advanced and Distributed Simulation (PADS'05)
DOI: 10.1109/pads.2005.21
|View full text |Cite
|
Sign up to set email alerts
|

Requirements on Worm Mitigation Technologies in MANETS

Abstract: This study presents an analysis of the impact of mitigation on computer worm propagation in Mobile Ad-hoc Networks (MANETS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…The research community has already started to investigate the feasibility and the propagation dynamics of worms in mobile networks [5,6,34,29]. While no large-scale mobile worm outbreak has been reported so far, several reports of worms spreading over the Bluetooth protocol in a cell-phone environment exist [7,12].…”
Section: Slowing the Spread Of Wormsmentioning
confidence: 99%
“…The research community has already started to investigate the feasibility and the propagation dynamics of worms in mobile networks [5,6,34,29]. While no large-scale mobile worm outbreak has been reported so far, several reports of worms spreading over the Bluetooth protocol in a cell-phone environment exist [7,12].…”
Section: Slowing the Spread Of Wormsmentioning
confidence: 99%
“…Our result is consistent with the findings in [12] which show that epidemiological models greatly overestimate the spreading rate of worms in MANET. On the other hand they refute the findings in a preliminary study of worm spreading in VANET [13].…”
Section: The Spreading Of Unknown Wormssupporting
confidence: 93%
“…A worm attack on VANET may interfere with critical applications such as engine control and safety warning systems hence resulting in serious congestion on the road networks and large-scale accidents. While there has been much research on the dynamics of worm spreading on the Internet [10,9,11], there has been, to our knowledge, very few studies of worm epidemics in mobile ad hoc network in general [12] and vehicular ad hoc networks in particular [13]. Such studies are critical for assessing the risks associated with worm attacks on VANET, and devising effective counter measures and techniques for their detection and mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…The most relevant work to this paper is [3] and [4]. In [3] the authors investigated the impact of communications and mobility effects on worm propagation mechanisms in MANETs, where they found that network delays and channel congestion had a large impact on the UDP-based worm propagation behavior.…”
Section: Related Workmentioning
confidence: 99%
“…They also provided a set of relatively simple analytical models that reproduced these communications. In [4] the authors discussed the effect of mitigation techniques on the UDPbased worm spread in MANETs and provided analytical models and simulation experiments to validate their findings. The authors represented the mitigation technologies as having a constant detection time represented by a lifetime parameter of the worm, after which the worm dies and stops infection of other hosts.…”
Section: Related Workmentioning
confidence: 99%